2017
DOI: 10.7575/aiac.ijels.v.5n.2p.74
|View full text |Cite
|
Sign up to set email alerts
|

Students and Teachers’ Perceptions into the Viability of Mobile Technology Implementation to Support Language Learning for First Year Business Students in a Middle Eastern University

Abstract: Advancements in technology have enabled us to learn, adapt and exploit our skills and knowledge in new ways.  Appreciating the potential of technology may yet give growth and enrich the process of language education, particularly through a student-centred mobile learning environment. Consequently, a constructivist approach to learning can create tremendous possibilities for both language learners and teachers. By exploiting the affordances of mobile technologies and the Internet, a new platform of learning or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 27 publications
2
25
0
Order By: Relevance
“…Especially the use of MALL can bring positive changes in the performance of learning by flourishing new and revolutionary opportunities that can develop latest pedagogical methods in learning. These latest scaffoldings will make learning of language possible beyond restriction of place and time while helping the students to improve their motivation and participation and thus creating a student-centered ambiance (Tayan, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Especially the use of MALL can bring positive changes in the performance of learning by flourishing new and revolutionary opportunities that can develop latest pedagogical methods in learning. These latest scaffoldings will make learning of language possible beyond restriction of place and time while helping the students to improve their motivation and participation and thus creating a student-centered ambiance (Tayan, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…According to the findings by Liu et al [8], the knowledge content should be clear, concise and refined to reflect the smartphones interface features, as well as to provide effective learning experiences. In addition, Tayan [9], in his research study, reported that MALL facilitates autonomous learning and better collaboration in a richer learning environment.…”
Section: Introductionmentioning
confidence: 99%
“…Research also shows that students are more motivated to learn when using mobile devices [9][10][11][12]. For instance, the findings by Tayan [9] showed that 85% of university students and 100% of teachers thought that mobile learning could act as a motivational stimulus for learning a foreign language.…”
Section: Introductionmentioning
confidence: 99%
“…Students also benefits from memorizing vocabulary through their cellphones so that they are ultimately able to motivate learning vocabulary. As a good and modern learning tool, MALL has also contributed to learenrs' independent learning (Tayan, 2017) especially for language learners in business schools in the Middle East. The independence and autonomy of learning are important to be optimized because intelligence developed along with the efforts of individual who has strong willingness to optimize their learning potential.…”
Section: Discussionmentioning
confidence: 99%
“…The last feature of service is the role of the teacher in accessibility that is internal and external in the school environment. Optimizing internal access must be related to opportunities for access to the existing schools in optimizing the individual role of students during the learning process (Tayan, 2017;Branden, 2006). Internal school access is certainly related to the utilization of all school facilities; classrooms, libraries, laboratories, playgrounds, sports facilities etc.…”
Section: Literature Reviewmentioning
confidence: 99%